Detection of intercontinental reassortant H6 avian influenza viruses from wild birds in South Korea, 2015 and 2017 - Kim, Ji-Yun; Lee, Sun-Hak; Kim, Da-Won; Lee, Dong-Wook; Song, Chang-Seon; Lee, Dong-Hun; Kwon, Jung-Hoon (Frontiers in Veterinary Science, 2023)
Avian influenza viruses (AIVs) in wild birds are phylogenetically separated in Eurasian and North American lineages due to the separated distribution and migration of wild birds. However, AIVs are occasionally dispersed between two continents by migratory wild birds flying across the Bering Strait. In this study, we isolated three AIVs from wild bird feces collected in South Korea that contain gene segments derived from American lineage AIVs, including an H6N2 isolated in 2015 and two H6N1 in 2017. Phylogenetic analysis suggests that the H6N2 virus had American lineage matrix gene and the H6N1 viruses had American lineage nucleoprotein and non-structural genes. These results highlight that novel AIVs have continuously emerged by reassortment between viruses from the two continents. Therefore, continuous monitoring for the emergence and intercontinental spread of novel reassortant AIV is required to prepare for a possible future outbreak.